Connection Failure: War, Spiritualism, and Communications Media in Violet Hunt's "Love's Last Leave". Issue 2 (3rd April 2022) - Dinsman, Melissa; Robinson, Heather
ABSTRACT: An overlooked figure of modernist circles, Violet Hunt was a suffragette, novelist, and author of ghost stories. In her second collection of haunted narratives, More Tales of The Uneasy (1925), Hunt explores the ghostliness of the Great War, both for those on the front and at home. In this essay, we focus on the third story in this volume, "Love's Last Leave", and argue that Hunt includes both ghost story tropes and communications media to articulate the real deadliness of the Great War. Communications technology and spiritualism share a similar historical evolution, and in "Love's Last Leave" both types of medium fail to connect those at home with those "who are gone". By re-narrating the shared history of spiritualism and communications media, Hunt implies the devastation and deadliness of war even when the plot fails to do so. In this essay, we use media theory and narratology to show how the gaps, absences, and uncertainties in the story's narrative structure are replicated by the communications technology in the story. The failure of narrative, technological, and spiritual mediums to transmit clear messages throughout "Love's Last Leave" emphasizes how deadly the disconnect between sender and receiver can be.